Evaluation of serum lipoprotein(a) level in type 2 diabetic patients and non-diabetic people - Karmakar, Pijush; Zohora, Fatema Tuz; Farzana, Taposhi (International Journal of Research in Medical Sciences, 2022)
Background: Type 2 diabetes mellitus has high morbidity and results in increased risk of mortality mainly due to cardiovascular diseases. Different factors have been found to be responsible for the increased prevalence of coronary artery disease in T2DM. One of these factors includes raised serum level of lipoprotein(a) (Lp(a)). The purpose of the present study is to assess the serum level of Lp(a) in type 2 diabetes mellitus patients and non-diabetic people with find the difference of serum Lp(a) between good and poor glycaemic control. Methods: This cross-sectional study was carried out in the department of Biochemistry and Endocrinology, Chittagong Medical College Hospital, Chattogram from July 2017 to June 2018. We assess a total of 100 type 2 diabetic patients and a group of 50 non-diabetic people with the age range 31-60 years. Blood samples were collected in fasting state and analysed for FPG, HbA1c%, serum lipid profile (TC, TG, LDL & HDL) and Lp(a). Data were analysed by T-test and chi-square test. Results: The serum Lp(a) levels were significantly elevated in type 2 diabetic patients compared to non-diabetic people (44.32±2.6 vs. 13.02±0.81). There were also significant difference of serum Lp(a) between good and poor glycaemic control. Conclusions: Lp(a) is an independent risk factor for atherosclerosis and has elevated level in diabetic patients. So, selective screening with lowering its concentration would help prevention of coronary artery disease, a known cause of death in diabetic patients.